Mengurai Dimensi Kemiskinan di Riau: Pendekatan Multidimensional dan Dampaknya pada Pembangunan - Widayatsari, Any; Harlen, Harlen; Damaiyanti, Desi; Misdawita, Misdawita (UI Scholars Hub, 2025)
Poverty issues have always been in the world spotlight. Monetary poverty measurements are considered only to be able to capture a small part of the various poverty issues, so measurements involving multidimensions are needed. This study attempts to measure poverty based on multiple levels of deprivation experienced by people in Riau Province. This study uses aspects of health, education, and standard of living. The results of the study show that all indicators simultaneously have a significant impact on monetary poverty. These indicators are calorie and protein consumption, length of schooling, school sustainability, and housing-related indicators. In addition, differences were also found in the picture of poverty measured only by considering monetary aspects and poverty measured using multidimensional aspects.